(untitled) (Journal of Biomedical Investigation, 2023)
Background: Inflammatory bowel disease (IBD) is characterized by prolonged symptomatic episodes of risk of relapse and remission. Current diagnosis of IBD rely heavily on use of faecal biomarkers such as faecal calprotectin (fCAL) which has been noted to have certain limitations. Quantitative determination of levels of fCAL through the application of enzyme–linked immunosorbent assay (ELISA) technique is well–established. Aim: The primary goal of this study was to develop and validate S100A12 ELISA (ImmunodiagnostikTM AG, Stubenwald–Allee 8a, D–64625 Bensheim, Germany) for the determination of S100A12 in serum (sA12), and to validate MRP8/14 Calprotectin S100A8/A9 ELISA (Bühlmann Laboratories AG, Baselstrasse 55, CH–4124 Schönenbuch, Switzerland) and IDK® Calprotectin ELISA (ImmunodiagnostikTM AG, Stubenwald–Allee 8a, D–64625 Bensheim, Germany) for the determination of calprotectin in serum (sCAL). Method: The assay was validated by determining sensitivity, linearity, recovery, imprecision, carry over, analytical interference and stability. A two–site sandwich enzyme–linked immunosorbent assay (ELISA) was developed and analytically validated using faecal and serum samples from healthy controls and patients presenting with inflammatory bowel disease directed against commercially available ELISA kits manufactured by Bühlmann Laboratories AG, Schönenbuch, Switzerland and ImmunodiagnostikTM AG, Bensheim, Germany. To accomplish this goal, a two–site sandwich ELISA for serum S100A12 and faecal calprotectin was set up and validated by evaluating faecal S100A12 ELISA assay for use with serum S100A12 samples, and faecal calprotectin ELISA assay for use with serum calprotectin samples. Results: Linearity versus recovery data for BMN®-Cp (100.8 vs. 82.1%), IDK®-Cp (98.4 vs. 89.5%) and IDK®-A12 (103.7% vs. 107.8%) are within the target of between 80–120% acceptance criteria for immunoassays. %CV for intra–assay versus inter–assay variability for BMN®-Cp (3.1 vs. 3.2), IDK®-Cp (2.9 vs. 4.7) and IDK®-A12 (7.0 vs. 3.8) are <20% acceptable criteria for imprecision study.ULMR for BMN®-Cp, IDK®-Cp and IDK®-A12 were 2.4x106, 2.5x104 and 5.4x102 ng/mL respectively. LoB versus LLoD were 577 vs. 597, 0.673 vs. 1.119 and 1.145 vs. 1.633 ng/mL for BMN®-Cp, IDK®-Cp and IDK®-A12 respectively. LoQ was 3615, 2880 and 522 ng/mL for BMN®-Cp, IDK®-Cp and IDK®-A12 respectively. No significant assay drift, carry over or instability was observed for the assays. Conclusion: The assays described are sufficiently sensitive, linear, accurate, precise and `reproducible for routine clinical laboratory application. Further studies to evaluate the clinical utility of the assays in assessing IBD are needed.